Facile storage and release of white phosphorus and yellow arsenic - Andreas E. Seitz (Nature Portfolio, 2018)
White phosphorus and yellow arsenic represent useful elemental sources for synthetic applications, but their poor stabilities make their storage highly challenging. Here, Scheer and colleagues encapsulate P4 and As4 molecules within porous activated carbons and demonstrate their use in subsequent chemical reactions.